Organizational-administrative Features of the Implementation of Educational Services in the Two-level System of Training of Highly Qualified Personnel - Saprykina, Vera Y.; Lashko, Sergey I.; Klochko, Elena N.; Yarushkina, Elena A.; Chumakova, Natalia A.; Bugaenko, Vladlena E. (International Journal of Economics and Financial Issues, 2016)
It is education - the system of formation of the nation’s intellectual capital and as one of the main areas of production innovation - creating the basic conditions for intensive growth of the markets on the basis of rapid updating of technologies and products. Education acts as the first link "education - research - innovation development of mass" of the innovation cycle. This educational sphere acts not only as a necessary element of reproduction of intellectual capital, but also as a dominant element of economic growth, which determines the stability of the external and internal competitive advantages of national economic systems. From the power of the national economy play an individual and a public intellectual capital, which implements the level of economic thinking of the nation, it is largely determined by economic strength, well-being, and the choice of its strategy and the subsequent trajectory of development in a global world order. In this connection, the Russian education there are urgent tasks related to the need to comply with the transformation of the education sector changes. Keywords: economic growth, educational service, training, educational organization JEL Classifications: G20, L00, O40